1982
DOI: 10.1111/j.1432-1033.1982.tb05840.x
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Pairs of Peptides Related to Melanotropin, Corticotropin and Endorphin in the Pars Intermedia of the Amphibian Pituitary Gland

Abstract: This study concerns the biosynthesis of a number of peptides in the neurointermediate lobe of the pituitary gland of the aquatic toad, Xenopus laevis. Using pulse-chase incubations in virro and high-performknce liquid chromatographic analysis, it could be shown that these peptides are synthesized through processing of a prohormone, pro-opiomelanocortin; all peptides were released into the incubation medium. On the basis of electrophoretic analysis, selective amino acid incorporation and immunoprecipitation, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…The fact that both tilapia forms are released into the medium might indicate differential processing of POMC in the corticotropes of this species, possibly leading to phosphorylated and nonphosphorylated forms (Ben nett et al, 1983) or to molecules of varying size (e.g., by carboxypeptidase activity; Friedman et al, 1993). The possibility that one of the forms represents POMC can be excluded, since the prohormone elutes at 41 min in the HPLC system used (Martens et al, 1982). Different degrees of glycosylation appear unlikely on the basis of the data by Iturriza and Estivariz (1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that both tilapia forms are released into the medium might indicate differential processing of POMC in the corticotropes of this species, possibly leading to phosphorylated and nonphosphorylated forms (Ben nett et al, 1983) or to molecules of varying size (e.g., by carboxypeptidase activity; Friedman et al, 1993). The possibility that one of the forms represents POMC can be excluded, since the prohormone elutes at 41 min in the HPLC system used (Martens et al, 1982). Different degrees of glycosylation appear unlikely on the basis of the data by Iturriza and Estivariz (1986).…”
Section: Discussionmentioning
confidence: 99%
“…Reverse-phase high-performance liquid chromatog raphy was performed as described by Martens et al (1982). To the fractions collected, 10 |xg BSA was added, and the samples were dried in a Speedvac (Sa vant).…”
Section: Hplcmentioning
confidence: 99%
“…Analysis of biosynthetic events in neurointermediate lobes of X. laevis showed that the production of melanotropins has the characteristics of a precursor-product relationship (Loh and Gainer, 1977;Jenks and van Overbeeke, 1980). In vitro and in vivo studies by Martens et al (1980Martens et al ( , 1982aMartens et al ( -c, 1983 revealed that in Xenopus the biosynthesis commences with the production of a prohormone, pro-opiomelanocortin (POMC) which is subsequently processed to yield three melanotropic peptides, namely, a-MSH, des-N-a-acetyl-ol-MSH, and a y,-MSH-like peptide, as well as several other peptides, including two forms of a corticotropin-like intermediate peptide (CLIP) and two peptides structurally related to the endogenous opiate B-endorphin. Analysis of release showed spontaneous secretion of all these peptides with the exception of des-N-a-acetyl-a-MSH which was acetylated to form a-MSH during the release process (Martens et al, 1981a).…”
mentioning
confidence: 99%
“…Evidence already has been provided for two distinct proopiomelanocortin-related precursors in the pituitary of fish and amphibians (31,32 [Met]enkephalinArg6-Gly7-Leu8 was detected, significant octapeptide immunoreactivity (>10 pmol/g) was present in higher molecular weight peptide(s) (Mr 2,000-3,000). Thus, avian proenkephalin is also closely related to the mammalian precursor.…”
mentioning
confidence: 99%